Digital Prenuptial Agreement through Electronic Notary in Indonesian Legal System - Syafruddin, A. Ummu Fauziyyah; Tombi, Johan Tri Noval Hendrian; Raden, Andi Nur Fikriana Aulia; Ulil Amri (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2025)
Implementing digitalization in prenuptial agreements will still face many challenges, such as the readiness of digital infrastructure for notaries, public legal awareness, and guarantees related to personal data protection. Therefore, studying the legality and practice of digital prenuptial agreements through electronic notaries is important to provide legal certainty in the Indonesian legal system, which continues to undergo significant developments over time. This study employs a normative legal method with a legislative, case, and conceptual approach to analyze the urgency of legal recognition for prenuptial agreements through electronic notaries. The findings indicate that implementing the Remote Notary concept in Indonesia is not possible under current law, as the concept utilizes electronic tools as a means of communication, such as teleconferencing or video calls, which would inevitably impact the process of reading and signing the deed. Existing legal provisions do not fully support the legitimacy of electronic notarial deeds, particularly because they still require the physical presence of the parties and witnesses. Article 16(1)(m) of the Notary Public Act contradicts cyber notary practices, while the Electronic Information and Transactions Law explicitly excludes notarial deeds from the category of valid electronic documents. This makes digital prenuptial agreements vulnerable to being classified as private documents with weaker legal standing. Therefore, comprehensive regulatory harmonization efforts are needed to integrate principles of civil law, marriage law, and advancements in information technology.